Two men, one possibly Siberian Eskimo, and one in a Russian military uniform, on deck of ship, probably Aleutian Islands, approximately 1899 - Warner, Arthur Churchill, 1864-1943 (1899)
This photograph was probably taken aboard ship somewhere in the Russian Aleutian Islands. Warner [2109] Filed in Alaska series.